Analisis Determinan Keberhasilan Usaha Kecil dan Menengah (UKM) di Kota Pekanbaru - Marlina, Evi; Sari, Ayu Indah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This research examines the influence of human resources (HR), digital marketing, business capital, and the use of accounting information on the success of SMEs. The population of this research is all SMEs in the Pekanbaru city area. The Slovin formula was used to determine the number of research samples and obtained 100 samples. Questionnaires were distributed directly to SMEs as research respondents. The analysis method uses multiple regression and the data is processed using the SPSS version 22 application. The research results show that HR, digital marketing, and PIA significantly affect the success of SMEs. In contrast, business capital does not have a significant effect on SMEs in Pekanbaru.